2022
DOI: 10.1111/ejn.15653
|View full text |Cite
|
Sign up to set email alerts
|

A co‐expression network based molecular characterization of genes responsive for Braak stages in Parkinson's disease

Abstract: The progression of Parkinson's disease (PD) is defined by six Braak stages. We used transcriptome data from PD patients with Braak stage information to understand underlying molecular mechanisms for the progress of the disease. We created networks of genes with continuously decreased/increased co‐expression from control group to Braak 5–6 stages. These networks are significantly associated with PD‐related mechanisms such as mitochondrial dysfunction and synaptic signalling among others. Applying weighted gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…A previous study has suggested that neuroactive ligand-receptor interactions may play an important role in the process of PD; meanwhile, Slc18a2, GRIN1 and GRIN2D may be potential candidate genes for PD progression. 46,47 Another metabolite, dopamine, an intermediate product of tyrosine metabolism should also be mentioned. The state of striatal dopamine release is of considerable importance in the diagnosis and research of PD.…”
Section: Food and Function Papermentioning
confidence: 99%
“…A previous study has suggested that neuroactive ligand-receptor interactions may play an important role in the process of PD; meanwhile, Slc18a2, GRIN1 and GRIN2D may be potential candidate genes for PD progression. 46,47 Another metabolite, dopamine, an intermediate product of tyrosine metabolism should also be mentioned. The state of striatal dopamine release is of considerable importance in the diagnosis and research of PD.…”
Section: Food and Function Papermentioning
confidence: 99%